Long‐term outcome of renal transplantation in childhood‐onset anti‐neutrophil cytoplasmic antibody–associated vasculitis - Nagasawa, Takeshi; Miura, Kenichiro; Kaneko, Naoto; Yabuuchi, Tomoo; Ishizuka, Kiyonobu; Chikamoto, Hiroko; Akioka, Yuko; Hisano, Masataka; Hattori, Motoshi (Pediatric transplantation, 2020)
Background There have been a few reports of RTx for AAV in children; however, post‐transplant recurrence rate and long‐term prognosis remain unclear. Here, we describe the long‐term outcomes of RTx in childhood‐onset AAV. Methods We conducted a retrospective study of children who underwent RTx for AAV between 1999 and 2017 and had a follow‐up period of >2 years. Results Seven patients consisting of three children with MPA and four with RLV were analyzed. Age at Dx was 5.9 (median; range, 4.1‐14.5) years. PD was instituted in all patients, and median time on dialysis was 26 (range, 14‐63) months. Age at RTx was 12.8 (median; range, 8.7‐16.3) years. There were no recurrences of AAV noted during the median follow‐up period of 7.0 (range, 2.7‐18.8) years after RTx. Graft loss occurred in one patient due to non‐adherence. Estimated glomerular filtration rate of the remaining patients at the last follow‐up was 73.0 (median; range, 50.7‐93.9) mL/min/1.73 m2. No malignancies and deaths occurred during the observational period. Conclusions Our study suggests that RTx for AAV with ESRD is a potentially safe and effective treatment choice for children with AAV.